AB0894 Hight Resolution Consultation of a Bone Metabolism Unit (BMU). First Year Results. (9th June 2015) - Chamizo, E.; Mellado, L.M.; Rojas, S.M.; Veroz, R.; Rodríguez Araya, T.L.; Aznar, J.J.
Abstract : Background: Osteoporosis (OP) is a silent disease until fractures appear. The controversy in diagnosis and treatment results in a variability in the management and a high frequency in consultation. In 2013 we started in collaboration with Primary Care (PC) a high resolution consultation to unify the management of OP in Merida and the surrounding area in the west of Spain. Objectives: Describe the characteristics of the population attended during the first year in the high resolution consultation of OP, from July 2013 to June 2014. Methods: We systematically collect the data of the interview oriented by clinical risk factors of OP, calculation of fracture risk (FRAX) before and after of the Bone Mineral Densitometry (BMD), blood analysis with levels of vitamin D, lumbar spineBMD (L2-L4) and hipBMD (femoral neck), lateral radiography of dorsolumbar spine and treatment, all performed in the same visit. Results: 355 patients were attended to with a mean age of 64.13 years old (95%CI 62.89; 65.37), coming from PC 277 (78%), and Specialized Care (SC) 78 (22%), mainly Oncology (23) with suspicion of OP. The characteristics of the population can be seen in the figure 1. Of the 277 patients coming from PC, 104 were treated for OP (mainly with biphosphonates) and 67 hadn't been diagnosed with OP. In the evaluation we detected fractures in 15 patients and FRAX- hipBMD>3 in 17 patients and 46 patients didn't need treatment because they were found not to have OP. The other 172 patients hadn't received any previous treatment, 4 of them had diagnosis of OP (previous BMD) and 2 had one fracture. After the study, we detected a FRAX-hipBMD>3 in 32 patients and we started immediatly treatment in 53 patients. Conclusions: High resolution consultation of OP has improved the accessibility of the patients from PC, has decreased the number of displacements and the number of consultations because the all the procedures are done on the same day. The systematic use of the clinical risk factors and the BMD helps practitioners decrease the variability in the diagnosis and treatment as shows the interruption of 43 treatment and the establishment of 53. Disclosure of Interest: None declared